2018
DOI: 10.1111/nph.15379
|View full text |Cite
|
Sign up to set email alerts
|

A neglected alliance in battles against parasitic plants: arbuscular mycorrhizal and rhizobial symbioses alleviate damage to a legume host by root hemiparasitic Pedicularis species

Abstract: Despite their ubiquitous distribution and significant ecological roles, soil microorganisms have long been neglected in investigations addressing parasitic plant-host interactions. Because nutrient deprivation is a primary cause of host damage by parasitic plants, we hypothesized that beneficial soil microorganisms conferring nutrient benefits to parasitized hosts may play important roles in alleviating damage. We conducted a pot cultivation experiment to test the inoculation effect of an arbuscular mycorrhiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 54 publications
3
36
0
Order By: Relevance
“…Interestingly, Wu et al indicated that inoculation of rice with one species of rhizobia, Sinorhizobium meliloti, helped rice growth by elevating the expression of genes that function to enhance cell expansion and accelerate cell division [41]. Furthermore, another study revealed that the alliance of arbuscular mycorrhizal (Glomus mosseae) and rhizobial (R. leguminosarum) symbioses alleviated damage to clover (Trifolium repens) by root hemiparasitic Pedicularis species [42].…”
Section: Plant Growth-promoting Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Wu et al indicated that inoculation of rice with one species of rhizobia, Sinorhizobium meliloti, helped rice growth by elevating the expression of genes that function to enhance cell expansion and accelerate cell division [41]. Furthermore, another study revealed that the alliance of arbuscular mycorrhizal (Glomus mosseae) and rhizobial (R. leguminosarum) symbioses alleviated damage to clover (Trifolium repens) by root hemiparasitic Pedicularis species [42].…”
Section: Plant Growth-promoting Bacteriamentioning
confidence: 99%
“…Interestingly, Wu et al indicated that inoculation of rice with one species of rhizobia, Sinorhizobium meliloti, helped rice growth by elevating the expression of genes that function to enhance cell expansion and accelerate cell division [41]. Furthermore, another study revealed that the alliance of arbuscular mycorrhizal (Glomus mosseae) and rhizobial (R. leguminosarum) symbioses alleviated damage to clover (Trifolium repens) by root hemiparasitic Pedicularis species [42]. The N2-fixing Frankia, one genus belonging to the actinobacteria group, form the actinorhizal nodules with actinorhizal plants, and promote the growth and abiotic resistance for several woody plants, such as Alnus rubra, Hippophae tibetana, Elaeagnus angustifolia, and Casuarina glauca [30,[43][44][45][46].…”
Section: Plant Growth-promoting Bacteriamentioning
confidence: 99%
“…Additionally, studies of Cuscuta have shown that the functional haustorium transfers macromolecules such as mRNAs, proteins, secondary metabolites and small RNAs, as well as pathogens such as phytoplasma and viruses (Kim & Westwood, 2015;Shahid et al, 2018). Although growth stimulation after attachment to a host has been observed in several facultative parasites (Klaren & Janssen, 1978;Sui et al, 2019), changes in parasites before and after attachment to a host have rarely been experimentally tested (Li et al, 2012). The microscopic structures of haustoria have been the focus of investigation in root hemiparasites (Zhang et al, 2012), whereas investigations of microscopic structures of leaves and stems have received comparatively little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Plants are engaged with a wide range of beneficial fungi that provide plant with various benefits, for instance, enhanced root system growth (Sukumar et al, ; Zhang et al, ), increased water and nutrient uptake (Almario et al, ; Ezawa & Saito, ), and better stress tolerance (Sui, Zhang, Tian, Xue, & Li, ) in exchange for photoassimilates. Root beneficial fungi have also been demonstrated to influence the timing of important developmental transitions, especially flowering (Das et al, ;Pan et al, ; Zavala‐Gonzalez et al, ).…”
Section: Introductionmentioning
confidence: 99%